Consumption of fruits and vegetables associated with other risk behaviors among adolescents in Northeast Brazil - Fabiana Medeiros de Almeida Silva; Aldemir Smith-Menezes; Maria de Fátima da Silva Duarte
Abstract Objective: To determine the prevalence of consumption of fruits and vegetables and identify the association with low level of physical activity, exposure to sedentary behavior, consumption of soft drinks and overweight/obesity in adolescents. Methods: This is a cross-sectional school-based study with a representative sample of 3992 students aged 14-19 years from the state of Sergipe, Brazil. The outcome was low consumption of fruits and vegetables (<5servings/day). Independent variables were: level of physical activity, sedentary behavior, consumption of soft drinks, and overweight/obesity. Global Student Health Survey questionnaire and body mass and height measurements were used, as well as chi-square test and crude and adjusted binary logistic regression. The significance level adopted was 5%. Results: The prevalence of inadequate consumption of fruits and vegetables was high - 88.6% (95%CI=87.6-89.5). Higher likelihood of low consumption of fruits and vegetables was verified among boys who were exposed to sedentary behavior (OR=1.63; 95%CI=1.18-2.24), who consumed soft drinks (OR=3.04; 95%CI=2.10-4.40), with insufficiently physical activity (OR=1.98; 95%CI=1.43-2.73) and girls who consumed soft drinks (OR=1.88; 95%CI=1.43-2.47) and those with overweight/obesity (OR=1.63; 95%CI=1.19-2.23). Conclusions: There is a need of public policies aimed at encouraging the consumption of healthy foods among adolescents.